Promoting psychology to students: embracing the multiplicity of research foci and method - Rees, Clare S. (Frontiers in Psychology, 2013)
In order for the discipline of psychology to continue to thrive it is imperative that future students are effectively recruited into the field. Research is an important part of the discipline and it is argued that the nature of psychological research is naturally one of multiplicity in topic and methodology and that promoting and highlighting this should be considered as a potentially effective recruitment strategy. In this study, a snap-shot of current research topics and methodologies was collected based on published papers from one typical academic psychology department in Australia. Fifty articles published in the period 2010-2013 were randomly selected and then grouped using content analysis to form topic clusters. Five main clusters were identified and included: Grief and Loss; Psychopathology; Sociocultural Studies; Attachment and Parenting; and Developmental Disorders. The studies spanned the full spectrum of research methodologies from quantitative to qualitative and had implications for assessment practices, diagnosis, prevention and treatment, education, and policy. The findings are discussed in terms of the unique characteristics of psychology as a discipline and how this diversity ought to be utilized as the main sell